ANEUK MEUDAGANG TRADITION IN DAYAH: A STUDY ON SANTRIWATI MEUDAGANG AT DAYAH AL-IKHLAS - Karnila Nazaruddin; Ajidar Matsyah (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2021)
This article is about